2016
DOI: 10.1177/0269215515628038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inspiratory muscle training on pulmonary function, respiratory muscle strength and functional capacity in patients with atrial fibrillation: a randomized controlled trial

Abstract: Inspiratory muscle training can improve pulmonary function, respiratory muscle strength and functional capacity in patients with atrial fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 34 publications
(45 reference statements)
4
27
0
4
Order By: Relevance
“…The Preferred Reporting Items for Systematic Reviews and Meta-Analyses flow diagram (figure 1) describes the selection process. Nine studies (nine publications) were included in this analysis2 10 25–31 (see table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Preferred Reporting Items for Systematic Reviews and Meta-Analyses flow diagram (figure 1) describes the selection process. Nine studies (nine publications) were included in this analysis2 10 25–31 (see table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence from pooled analysis of eight studies2 25–31 showed 52 deaths in 445 (11.7%) exercising participants and 47 deaths in 438 (10.7%) control participants. There was no significant difference in pooled RR between exercise-based CR and control groups (RR 1.08, 95% CI 0.77 to 1.53, p=0.64, I 2 =0%) (figure 2).…”
Section: Resultsmentioning
confidence: 99%
“… 9 , 10 Additionally, one study showed respiratory muscle weakness in patients with AF. 8 However, the pulmonary function of these patients and its contribution to the disease burden has not been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that most selected studies [12][13][14] have applied IMT protocols at 30% of the MIP for 30 minutes daily, for eight weeks. Many other works have shown that this training protocol promotes not only improvements in the respiratory muscle resistance and strength, but also in the functional capacity and quality of life of chronic disease patients 9,22 . These protocols, with more repetitions and less intensity, seem to elicit less exacerbated hemodynamic responses during the inspiratory muscle exercise, offering more safety for cardiovascular patients.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, Kaminski et al 14 have verified that IMT improved the ANS action on patients with the same disease, but with no diagnosis of respiratory muscle weakness. Unlike the interaction between inspiratory muscle weakness and IMT for the maximal inspiratory pressure (MIP) outcome, which indicates that the lower the pre-intervention MIP is, the higher the improvement observed after the training 21,22 , possibly, for these patients with bigger respiratory muscle force damage, the intensity and time of IMT application may have been insufficient to create the positive autonomic adaptations observed in other populations.…”
Section: Discussionmentioning
confidence: 99%